Permanent His bundle pacing and atrioventricular node ablation in a case with drug-refractory atrial fibrillation - Serkan Saygi; Emre Erturk; Caner Topaloğlu; Mohammed Abusharekh (KARE Publishing, 2019)
Permanent His bundle pacing (HBP) activates the ventricles through the normal conduction system and has become a useful technique for patients with a high ventricular pacing rate. Presently described is a case of drug-refractory atrial fibrillation (AF) with a high ventricular rate that was treated with atrioventricular (AV) node ablation and permanent HBP. A 62-year-old woman with persistent AF and a drug-refractory high ventricular response was referred for exercise intolerance and palpitation. She had a history of failed catheter ablation attempts and amiodarone toxicity. Permanent HBP and AV node ablation was planned to achieve rate control with a stepwise approach. Initially, implantation of a permanent pacemaker was performed. The His lead and right ventricular back-up leads were implanted successfully, in the manner described previously. The His lead was connected to the atrial channel of the pacemaker battery and programmed to AAI pacing mode. The AV node was ablated successfully 3 weeks later without any threshold changes in the His lead. No His lead threshold changes were observed during or after AV node ablation and the patient was subsequently asymptomatic with twice daily apixaban 5 mg. Permanent HBP after AV node ablation can be a beneficial treatment option to prevent pacing-induced ventricular dyssynchrony and heart failure in patients who are not eligible for cardiac resynchronization therapy.